Analyzing the features of wind turbines and photovoltaic cells from a 60-watt power generation - Omar Moftah Mayouf; Walid Aborid Abdannabi; Hatem. S. M. Mansour (African Journal of Advanced Pure and Applied Sciences, 2025)
The MATLAB Simulink software package is used in this research to create a generalized photovoltaic model that can be easily used on a simulation platform and is representational of PV cells, modules, and arrays. The suggested approach has a dialog box that resembles Simulink block libraries and an easy-to-use icon. This facilitates the simulation and analysis of the generalized PV model in combination with power electronics for a maximum power point tracker. The suggested model is used to simulate and optimize the PV model’s output current and power characteristics while accounting for the effects of solar irradiation and cell temperature. This makes it simple to simulate, evaluate, and optimize the dynamics of a PV power system. The Wind Energy Conversion System, or WECS for short, is a wind-driven power generation system that has been modeled and simulated. Our goal is to use MATLAB simulation to construct and test a 300W induction permanent magnet generator that operates between 3 and 6 meters per second. According to the project’s scope, the various parts of a wind energy system—the wind turbine, generator, and rectifier—were examined. The design process and system modeling were then carried out using the MATLAB simulation environment, Simulink.